Role of uterine forces in intrauterine device embedment, perforation, and expulsion - Goldstuck ND; Wildemeersch D (International Journal of Women's Health, 2014)
Norman D Goldstuck,1 Dirk Wildemeersch2 1Department of Obstetrics and Gynaecology, Faculty of Medicine and Health Sciences, Stellenbosch University and Tygerberg Hospital, Western Cape, South Africa; 2Gynecological Outpatient Clinic and IUD Training Center, Ghent, Belgium Background: The purpose of this study was to examine factors that could help reduce primary perforation during insertion of a framed intrauterine device (IUD) and to determine factors that contribute in generating enough uterine muscle force to cause embedment and secondary perforation of an IUD. The objective was also to evaluate the main underlying mechanism of IUD expulsion. Methods: We compared known IUD insertion forces for “framed” devices with known perforation forces in vitro (hysterectomy specimens) and known IUD removal forces and calculated a range of possible intrauterine forces using pressure and surface area. These were compared with known perforation forces. Results: IUD insertion forces range from 1.5 N to 6.5 N. Removal forces range from 1 N to 5.8 N and fracture forces from 8.7 N to 30 N depending upon device. Measured perforation forces are from 20 N to 54 N, and calculations show the uterus is capable of generating up to 50 N of myometrial force depending on internal pressure and surface area. Conclusion: Primary perforation with conventional framed IUDs may occur if the insertion pressure exceeds the perforation resistance of the uterine fundus. This is more likely to occur if the front end of the inserter/IUD is narrow, the passage through the cervix is difficult, and the procedure is complex. IUD embedment and secondary perforation and IUD expulsion may be due to imbalance between the size of the IUD and that of the uterine cavity, causing production of asymmetrical uterine forces. The uterine muscle seems capable of generating enough force to cause an IUD to perforate the myometrium provided it is applied asymmetrically. A physical theory for IUD expulsion and secondary IUD perforation is given. Keywords: IUD, insertion forces, removal forces, fracture forces, intrauterine pressure, intrauterine surface area